Determining normal and abnormal reference values for corrective osteotomy for congenital hand malformation: a study on the zone of provisional calcification and bone axis - Ahmad Zaki Barati; Anyuan Wang; Ismail Muhammad; Mazhar Ali Raza; Oumar Bussuma Boulama Abba; Weiyang Gao (Journal of Orthopaedic Surgery and Research)
Abstract Purpose This study aims to establish reference values for the normal bone axis in children to assess the effectiveness of corrective osteotomy procedures and guide the treatment of congenital hand malformations and post-operative axis deviations. Methods A retrospective study was carried out between January 1, 2022, and October 9, 2024. A total of 192 individuals were included. In both abnormal and normal individuals, we measured the angles within the zone of provisional calcification and the bone axis. The metacarpal, proximal, and distal phalanx of the thumb were measured in both males and females. We calculated the average and standard deviations for both groups. These normal reference values were then compared with the abnormal reference values of patients who had types II and IV polydactyly. Results Our work effectively established thorough reference values for the thumb's normal axis. Considering the success of corrective osteotomies in children with congenital deformities depends mostly on these values. In polydactyly type IV, we observed a change in the angle on the side with the axis deviation. Our results highlight the need for an exact preoperative design for thumb reconstruction. It also implies the possibility of choosing the side with little or no axis deviation during operation. This strategic selection can help prevent the need for additional osteotomies or subsequent surgeries. Conclusion Evaluating and preparing corrective osteotomy treatments benefits significantly from the reference values for the proper alignment of the thumb's bones. These results enable surgeons to predict the degree of corrective osteotomy needed, thereby improving postoperative surgical results and patient satisfaction.